Attitude and Behavior of the Coaches towards their Professions in the Context of Being Fair - Candide Uludağ, Candide (Advances in Social Sciences Research Journal, 2021)
Examining the attitudes and behaviors of coaches towards their profession in the context of being fair has been an important issue for both researchers and practitioners. The being fair of coaches in their profession can be broadly defined as the right action aimed at creating a positive impression. Research in this area can be developed to strengthen the theoretical basis by examining it in an organizational context in a consistent and effective manner. This research is a study of bringing the Fair Coaching Behavior (FCB) phenomenon to the literature within the scope of the theoretical literature review with the sample of coaches. The aim of the study is to determine the attitudes and behaviors of individuals who are coaching in their profession within the scope of fair behavior. Two different scenarios have been created for this. Firstly, an online questionnaire was applied to the participants who were coaching in the specified sectors and whose numbers are known. The second survey study was applied face-to-face this time, taking into account the same target audience, and questions including personal information were asked by one-on-one interviews with the participants. The second survey study was conducted four weeks after the first survey study. Thus, the attitudes and behaviors of the coaches towards their profession were examined in both different situations. Structural Equation Modeling was used in the analysis of the hypotheses predicted in the study. Composite Model of the Attitude-Behavior Relation (Eagly and Chaiken, 1993) was applied to explain FCB. Thus, it was aimed to obtain valuable information about the dynamics among the potential precursors of the fair behavior of coaches towards their professions with the help of predicted hypotheses. The three main results obtained in the research are as follows: (1) The Habit of Integrity is not an applicable direct or indirect premise of FCB. (2) In addition to the attitude towards FCB, the attitude towards the coaches' profession should be included in the FCB. (3) Idealistic Ethical Position was not observed in this study as an important predictor of the intention to be fair.